Soil water availability strongly modulates soil CO2 efflux in different Mediterranean ecosystems: Model calibration using the Bayesian approach - Correia, a C. C.; Minunno, F.; Caldeira, M. C. C.; Banza, J.; Mateus, J.; Carneiro, M.; Wingate, L.; Shvaleva, a; Ramos, a; Jongen, M.; Bugalho, M. N. N.; Nogueira, C.; et al. (Agriculture, Ecosystems & Environment, 2012)
Soil respiration in drought prone regions is highly dependent on the precipitation regime and soil moisture conditions, which are expected to change in a global warming context. In the present study we used an extensive collection of ﬁeld chamber measurements of soil respiration (Rs ) from forest and grassland sites of centre and south of Portugal distributed over a 10 year period. This data were summarized and analysed with the objective to describe seasonal variability of Rs as affected by soil moisture (Hs ) and soil temperature (Ts ). A Bayesian framework was used to test the effectiveness of soil bioclimatic models in estimating Rs on a daily and monthly time step. Rs seasonality was similar between sites, reaching a maximum in spring and autumn and a minimum in the dry season (July–September). No differences were observed for Rs between sites with different standing biomass or soil carbon stocks either on an annual or seasonal timescale. Hs , and not Ts , was the driving factor of Rs during most of the year. Ts drove Rs response only above certain Hs limits: 10% for forest sites and 15% for grassland sites leading to a Q10 of 2.01, 1.61 and 1.31 for closed forests, open forests and grasslands, respectively. The Bayesian analysis showed that models using Hs as an independent variable performed better than models driven by Ts alone. Monthly estimates of Rs in grasslands can be predicted by simple climatic models based on Hs but none of them was suitable for forest ecosystems, stressing the need for a process-based approach. This study adds to the evidence that Hs controls Rs ﬂuxes for Mediterranean ecosystems and should always be taken into account for extrapolation purposes.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Bayesian calibration; Empirical model; Mediterranean; Soil CO2 efﬂux; Soil moisture; Soil respiration; Soil temperature

N2O and CH4 fluxes in undisturbed and burned holm oak, scots pine and pyrenean oak forests in central Spain - Inclán, Rosa; Uribe, Carla; Sánchez, Laura; Sánchez, Dolores M.; Clavero, Ángeles; Fernández, Ana María; Morante, Ramón; Blanco, Alfredo; Jandl, Robert (Biogeochemistry, 2010)
We investigated N2O and CH4 ﬂuxes from soils of Quercus ilex, Quercus pyrenaica and Pinus sylvestris stands located in the surrounding area of Madrid (Spain). The ﬂuxes were measured for 18 months from both mature stands and post ﬁre stands using the static chamber technique. Simultaneously with gas ﬂuxes, soil temperature, soil water content, soil C and soil N were measured in the stands. Nitrous oxide ﬂuxes ranged from -11.43 to 8.34 lg N2O–N m -2 h -1 in Q.ilex, -7.74 to 13.52 lg N2O–N m -2 h -1 in Q. pyrenaica and -28.17 to 21.89 lg N2O–N m -2 h -1 in P. sylvestris. Fluxes of CH4 ranged from -8.12 to 4.11 lg CH4– C m -2 h -1 in Q.ilex, -7.74 to 3.0 lg CH4 –C m -2 h -1 in Q. pyrenaica and -24.46 to 6.07 lg CH4–C m -2 h -1 in P. sylvestris. Seasonal differences were detected; N2O ﬂuxes being higher in wet months whereas N2O ﬂuxes declined in dry months. Net consumption of N2O was related to low N availability, high soil C contents, high soil temperatures and low moisture content. Fire decreased N2O ﬂuxes in spring. N2O emissions were closely correlated with previous day’s rainfall and soil moisture. Our ecosystems generally were a sink for methane in the dry season and a source of CH4 during wet months. The available water in the soil inﬂuenced the observed seasonal trend. The burned sites showed higher CH4 oxidation rates in Q. ilex, and lower rates in P. sylvestris. Overall, the data suggest that ﬁre alters both N2O and CH4 ﬂuxes. However, the magnitude of such variation depends on the site, soil characteristics and seasonal climatic conditions.
Keywords: á; fire; greenhouse flux á fire; Greenhouse ﬂux; Pinus sylvestris; Quercus ilex; Quercus pyrenaica; quercus pyrenaica á pinus; Soil temperature; soil temperature á; Soil water content; soil water content á; sylvestris á

Drying and wetting of Mediterranean soils stimulates decomposition and carbon dioxide emission: the “Birch effect” - Jarvis, Paul; Rey, Ana; Petsikos, Charalampos; Wingate, Lisa; Rayment, Mark; Pereira, João; Banza, João; David, Jorge; Miglietta, Franco; Borghetti, Marco; Manca, Giovanni; Valentini, Riccardo (Tree Physiology, 2007)
Observations on the net carbon exchange of forests in the European Mediterranean region, measured recently by the eddy covariance method, have revived interest in a phenomenon first characterized on agricultural and forest soils in East Africa in the 1950s and 1960s by H. F. Birch and now often referred to as the “Birch effect.” When soils become dry during summer because of lack of rain, as is common in regions with Mediterranean climate, or are dried in the laboratory in controlled conditions, and are then rewetted by precipitation or irrigation, there is a burst of decomposition, mineralization and release of inorganic nitrogen and CO2. In forests in Mediterranean climates in southern Europe, this effect has been observed with eddy covariance techniques and soil respiration chambers at the stand and small plot scales, respectively. Following the early work of Birch, laboratory incubations of soils at controlled temperatures and water contents have been used to characterize CO2 release following the rewetting of dry soils. A simple empirical model based on laboratory incubations demonstrates that the amount of carbon mineralized over one year can be predicted from soil temperature and precipitation regime, provided that carbon lost as CO2 is taken into account. We show that the amount of carbon returned to the atmosphere following soil rewetting can reduce significantly the annual net carbon gain by Mediterranean forests.
10.1093/treephys/27.7.929
Keywords: carbon balance; carbon mineralization rates; Mediterranean climate; mediterranean forest; rain pulse; soil rewetting; Soil temperature; soil water; summer rainfall events

Drying and wetting of Mediterranean soils stimulates decomposition and carbon dioxide emission: the “Birch effect” - Jarvis, Paul; Rey, Ana; Petsikos, Charalampos; Wingate, Lisa; Rayment, Mark; Pereira, João; Banza, João; David, Jorge; Miglietta, Franco; Borghetti, Marco; Manca, Giovanni; Valentini, Riccardo (Tree Physiology, 2007)
Observations on the net carbon exchange of forests in the European Mediterranean region, measured recently by the eddy covariance method, have revived interest in a phenomenon first characterized on agricultural and forest soils in East Africa in the 1950s and 1960s by H. F. Birch and now often referred to as the “Birch effect.” When soils become dry during summer because of lack of rain, as is common in regions with Mediterranean climate, or are dried in the laboratory in controlled conditions, and are then rewetted by precipitation or irrigation, there is a burst of decomposition, mineralization and release of inorganic nitrogen and CO2. In forests in Mediterranean climates in southern Europe, this effect has been observed with eddy covariance techniques and soil respiration chambers at the stand and small plot scales, respectively. Following the early work of Birch, laboratory incubations of soils at controlled temperatures and water contents have been used to characterize CO2 release following the rewetting of dry soils. A simple empirical model based on laboratory incubations demonstrates that the amount of carbon mineralized over one year can be predicted from soil temperature and precipitation regime, provided that carbon lost as CO2 is taken into account. We show that the amount of carbon returned to the atmosphere following soil rewetting can reduce significantly the annual net carbon gain by Mediterranean forests.
10.1093/treephys/27.7.92910.1093/treephys/27.7.929
Keywords: carbon balance; carbon mineralization rates; Mediterranean climate; mediterranean forest; rain pulse; soil rewetting; Soil temperature; soil water; summer rainfall events

fructificación del hongo ECM comestible Amanita ponderosa Malençon & R. Heim durante seis años consecutivos en un encinar adehesado de la Sierra - Daza, A.; Camacho, M. (Investigación Agraria: Sistemas y Recursos Forestales, 2007)
Number and location of Amanita ponderosa Malençon & R. Heim sporocarps was followed through six years in a 3 ha holm-oak forest located in the Sierra de Aracena y Picos de Aroche Natural Park (Huelva), at the Southwest of Spain. The data indicated that patches of sporocarp production showed a very similar shape each year, but some spots showed differences seeming crop alternance or mast years. This species only fructifies in spring, being the fruiting period from 6 to 8 weeks, what coincides with the increasing of air-temperature from mid February to April. Differences in fruiting period length and total sporocarp production are related to rainfall and temperature. Results suggest that rainfalls at the end of summer and early autumn are crucial for the next spring fruiting, but rainfalls during fruiting period seem to have less influence in sporocarp production. During the sporocarp production period, it was related to soil temperature.
Keywords: gurumelo; mushroom harvest; raining; Soil temperature; sporocarp production and location

fructificación del hongo ECM comestible Amanita ponderosa Malençon & R. Heim durante seis años consecutivos en un encinar adehesado de la Sierra - Daza, a; Camacho, M (Investigación Agraria: Sistemas y Recursos Forestales, 2007)
Number and location of Amanita ponderosa Malençon & R. Heim sporocarps was followed through six years in a 3 ha holm-oak forest located in the Sierra de Aracena y Picos de Aroche Natural Park (Huelva), at the Southwest of Spain. The data indicated that patches of sporocarp production showed a very similar shape each year, but some spots showed differences seeming crop alternance or mast years. This species only fructifies in spring, being the fruiting period from 6 to 8 weeks, what coincides with the increasing of air-temperature from mid February to April. Differences in fruiting period length and total sporocarp production are related to rainfall and temperature. Results suggest that rainfalls at the end of summer and early autumn are crucial for the next spring fruiting, but rainfalls during fruiting period seem to have less influence in sporocarp production. During the sporocarp production period, it was related to soil temperature.
Keywords: gurumelo; mushroom harvest; raining; Soil temperature; sporocarp production and location

The key-role of topsoil moisture on CO$_2$ efflux from a Mediterranean Quercus ilex forest - Joffre, Richard; OURCIVAL, JEAN-MARC; Rambal, Serge; ROCHETEAU, ALAIN (Ann. For. Sci., 2003)
CO2 respiratory losses partly determine net carbon ecosystem exchanges. The main objective of this paper was to understand regulation imposed by soil water content and temperature on soil and ecosystem CO2 efflux in a holm oak (Quercus ilex L.) Mediterranean forest. Soil CO2 efflux was monitored monthly during 1999 and 2001. Moreover, experimental water treatments were conducted in 1999 over 9 small plots (0.3 m2) during nine months. Results showed strong decreases of soil CO2 efflux for a relative soil water content below 0.7. Ecosystem respiration measured by eddy covariance over a 4-year period showed strong sensitivity to soil water content and temperature. Severe limitations of soil and ecosystem efflux imposed by low values of soil water content occurred on about 90 days per year. The best adjustments of soil and ecosystem CO2 efflux were obtained using regression models where the exponential effect of temperature is linearly related to soil water content ( r2 = 0.68 and 0.79 for soil and ecosystem respectively). Our results highlighted strong differences in respiration sensitivity to topsoil moisture between soil and ecosystem. When the relative water content (RWC) is low (0.4), an increase of 1 °C provokes an increase of soil respiration of 5.7% and an increase of ecosystem respiration of 8.6%. For nonlimiting soil water conditions, at RWC = 1, the increases of respiration caused by a 1 °C temperature increase are of 8.5% and 16.5% for soil and ecosystem respectively. These results emphasized the probable determinant influences of changes in soil water regime for respiratory fluxes and net carbon exchanges of Mediterranean forest ecosystems.
Keywords: CO2 efflux; ecosystem respiration; Mediterranean ecosystem; Quercus ilex; Soil temperature; Soil water content